'See no evil': collusion in Northern Ireland. (January 2017) - McGovern, Mark
The publication of the official report into the 1994 Loughinisland massacre, when loyalist gunmen shot dead six people in a small, rural bar, provides an opportunity to examine the nature of institutionalised collusion, the state practices it involved and the sectarianised social order which made it possible during the conflict in Northern Ireland. Building on an earlier analysis of the colonial and counter-insurgency roots of collusion ( Race & Class, 57, no. 2) this article provides a commentary on the findings of the Loughinisland report and explores two issues. The first concerns new evidence (directly contradicting earlier official inquiries) of state collusion in the importation of arms used by loyalists to escalate their campaign of assassination in this period. Second, the extent to which collusive practices facilitated the actions of loyalist paramilitaries and confounded the investigation of the mass killings at Loughinisland as elsewhere. In terms of both, it will be argued, there is a need to place an understanding of collusion in the wider context of a social order shaped by long-term sectarianised social divisions and violence, embedded in localised power structures, which framed the very institutions and agencies of the state, not least the police and other state forces.